Increase of the Charge Transfer Rate Coefficients for NO+ and O2+• Reactions with Isoprene Molecules at Elevated Interaction Energies - Spesyvyi, Anatolii; Sovová, Kristýna; Smith, David; Španěl, Patrik (The journal of physical chemistry. A, 2018)
Atmospheric concentrations of isoprene (2-methylbutadiene) in environmental research and in exhaled breath for medical research are usually measured by soft chemical ionization mass spectrometry that relies on a knowledge of the kinetics of the gas phase reactions of H3O+, NO+ or O2+• ions with isoprene molecules. Thus, we have carried out an experimental study of the rate coefficients, k, and product ions distributions for such reactions over a range of ion-molecule interaction energy, Er, (0.05-0.8 eV) in a helium-buffered selected ion flow-drift tube, SIFDT. It is found that contrary to the ion-induced dipole capture model, k for the NO+ and O2+• charge transfer reactions almost doubled over the E r range, while k for the H3O+ proton transfer reaction did not significantly change with E r, as predicted. These results reveal that the reaction mechanism involving ion-molecule capture forming an intermediate complex does not properly describe charge transfer to isoprene molecules. It is important to account for this increase in k with E r in these isoprene charge transfer reactions, and probably for other such reactions, when using drift tube reactors for trace gas analysis.